Therapeutic efficacy of monthly subcutaneous injection of daclizumab in relapsing multiple sclerosis - Cohan S (Biologics: Targets & Therapy, 2016)
Stanley Cohan1,2,3 1Providence Multiple Sclerosis Center, 2Providence Brain and Spine Institute, 3Providence Health & Services, Portland, OR, USA Abstract: Despite the availability of multiple disease-modifying therapies for relapsing multiple sclerosis (MS), there remains a need for highly efficacious targeted therapy with a favorable benefit–risk profile and attributes that encourage a high level of treatment adherence. Daclizumab is a humanized monoclonal antibody directed against CD25, the α subunit of the high-affinity interleukin 2 (IL-2) receptor, that reversibly modulates IL-2 signaling. Daclizumab treatment leads to antagonism of proinflammatory, activated T lymphocyte function and expansion of immunoregulatory CD56bright natural killer cells, and has the potential to, at least in part, rectify the imbalance between immune tolerance and autoimmunity in relapsing MS. The clinical pharmacology, efficacy, and safety of subcutaneous daclizumab have been evaluated extensively in a large clinical study program. In pivotal studies, daclizumab demonstrated superior efficacy in reducing clinical and radiologic measures of MS disease activity compared with placebo or intramuscular interferon beta-1a, a standard-of-care therapy for relapsing MS. The risk of hepatic disorders, cutaneous events, and infections was modestly increased. The monthly subcutaneous self-injection dosing regimen of daclizumab may be advantageous in maintaining patient adherence to treatment, which is important for optimal outcomes with MS disease-modifying therapy. Daclizumab has been approved in the US and in the European Union and represents an effective new treatment option for patients with relapsing forms of MS, and is currently under review by other regulatory agencies. Keywords: daclizumab, disease-modifying therapy, humanized monoclonal antibody, relapsing multiple sclerosis, therapeutic use